The TPM in basic education schools. A case study - Egure Tovalín, Oralia; Reyes Ibarra, Blanca Emilia; Solís Campos, Alicia (IE Revista de Investigación Educativa de la REDIECH, 2022)
The objective of this qualitative research was to describe the technical pedagogical mentoring (TPM) approach in Durango, through the case study of the perceptions reflected from the individuals involved. Different authors were considered for the definition of pedagogical mentoring, as well as a contextualization in countries such as Chile, Paraguay, and Finland; in addition, legal aspects in Mexico were examined. The approach used was qualitative with a descriptive scope, using a case study methodology and semi-structured interviews as evaluation tools; six teachers, six pedagogical technical advisors and six supervisors, two from each educational level (preschool, elementary and high school) participated in the study. Among the main findings, no supervisor was allowed to choose his or her advisors; in addition, not all schools in each participating school zone were provided with mentoring, but they were chosen according to their development and specific needs. Nevertheless, the expectations of the pedagogical advisors, the supervisors and the teachers who received counseling were met.